NATURAL RESOURCE SCARCITY AND VIOLENT CONFLICT IN POST-NEW ORDER INDONESIA - Jalal, Asran; Lubis, Sahruddin (Journal of Social Political Sciences, 2025)
Natural resource scarcity and its nexus with violent conflict in Post-New Order Indonesia (1998–present) present a critical challenge to the nation’s democratic transition. As Indonesia embraced democratization, newfound political freedoms coincided with escalating disputes over land, forests, and mineral resources, often erupting into violence. This study evaluates the applicability of Homer-Dixon’s environmental scarcity theory to Indonesia’s context, probing two core questions: What drives environmental scarcity in Indonesia? and Why do land distribution conflicts resist resolution? Employing a qualitative approach, the research analyzes secondary data from online media reports, government documents, and NGO publications, utilizing content analysis to identify patterns in resource disputes across regions like Kalimantan, Sumatra, and Papua. Findings reveal that environmental scarcity stems from three interlinked factors: (1) demand-induced scarcity due to population growth and extractive industries; (2) supply-induced scarcity from ecological degradation (e.g., deforestation, mining); and (3) structural scarcity perpetuated by inequitable land ownership and weak governance. Despite democratic reforms, institutional fragmentation and corruption hinder conflict resolution, exacerbating tensions between communities, corporations, and local governments. For instance, palm oil expansion in Kalimantan has displaced indigenous groups, triggering protracted violence despite legal frameworks like the 2013 Indigenous Rights Law. The study concludes that Homer-Dixon’s theory partially explains Indonesia’s conflicts but underestimates the role of political economy and decentralization dynamics. Recommendations include strengthening land tenure transparency, decentralizing resource management, and integrating traditional ecological knowledge into policy.